TUTUR DALAM PROSESI LAMARAN PERNIKAHAN DESA JEPARA KECAMATAN BRR RANAU TENGAH - Dewi Puspita; Hetilaniar; Hayatun Nufus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speech in the marriage proposal procession is an important part of traditional communication that is full of cultural meaning and social values. This study aims to describe the form, function, and implicature of speech used in the traditional marriage proposal procession in Jepara Village, BPR Ranau Tengah District. A qualitative-descriptive approach was used with observation and interview methods, documentation and recording of the village head, traditional leaders, and the local community. The results of the study indicate that speech in the marriage proposal procession is indirect, subtle, and full of Ranau cultural symbols. There is the use of proverbs and traditional expressions that have a pragmatic function as a form of respect, expression of good intentions, and efforts to maintain harmony between families. Speech implicature shows a collective understanding of customary norms and values, such as respect, humility, and caution in conveying intentions.